Down syndrome preleukemia and leukemia. - Maloney, K; Taub, J; Ravindranath, Y; Roberts, I; Vyas, P (Elsevier, 2014)
Children with Down syndrome (DS) and acute leukemias acute have unique biological, cytogenetic, and intrinsic factors that affect their treatment and outcome. Myeloid leukemia of Down syndrome (ML-DS) is associated with high event-free survival (EFS) rates and frequently preceded by a preleukemia condition, the transient abnormal hematopoiesis (TAM) present at birth. For acute lymphoblastic leukemia (ALL), their EFS and overall survival are poorer than non-DS ALL, it is important to enroll them on therapeutic trials, including relapse trials; investigate new agents that could potentially improve their leukemia-free survival; and strive to maximize the supportive care these patients need.